Performance improvement in a sensorless surface-mounted PMSM drive based on rotor flux observer. (March 2020) - Marchesoni, Mario; Passalacqua, Massimiliano; Vaccaro, Luis; Calvini, Marco; Venturini, Marco
Abstract: Permanent magnet synchronous motor sensorless algorithms for low speed region are usually based on rotor anisotropy. Although many studies showed a good behavior of this type of control, high frequency voltage injection is required, which causes loud acoustic noise in addition to electrical losses. On the other hand, methods based on back electromotive force or rotor flux observer, which guarantee high performance in the medium–high speed region, do not required voltage injection. In this paper, a rotor flux observer based algorithm performance is analyzed, in order to extend its use also in the low speed region. Behavior both with no-load, linear torque, quadratic torque, constant torque and compressor-load torque is tested, especially focusing on motor starting. Improvements to rotor flux observer algorithms available in the scientific literature are discussed and their effectiveness is verified by experimental results. Highlights: Sensorless algorithm for PMSM based on Rotor Flux Observer is presented. A novel method to improve algorithm performance during transient is presented. Algorithm effectiveness with different loads and in different working conditions. Sensorless algorithm with rated torque at standstill.